2014
DOI: 10.3945/ajcn.113.070524
|View full text |Cite
|
Sign up to set email alerts
|

Associations of long-chain ω-3 fatty acids and fish intake with endometrial cancer risk in the VITamins And Lifestyle cohort

Abstract: The overall increased risk reported here confirms the findings of several prior observational studies of fish intake, which observed similar increases in risk. Randomized trials are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 44 publications
3
34
2
1
Order By: Relevance
“…Inverse associations are not supported by previous studies, which have found no associations between intakes of these fatty acids and risk of endometrial cancer (16,17,29).…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Inverse associations are not supported by previous studies, which have found no associations between intakes of these fatty acids and risk of endometrial cancer (16,17,29).…”
Section: Discussioncontrasting
confidence: 45%
“…Nevertheless, the reductions in risk we observed with high intakes of α-linolenic acid or linolenic acid in women with BMIs less than 25 complicate the interpretation of the LC ω-3 PUFA data. In previous studies, there was some evidence of an inverse association between LC ω-3 PUFA intake and risk of type I (i.e., endometrioid) endometrial cancers (16,17). Only 60% of endometrial cancer cases in the BWHS had medical record data available for abstraction of histological subtype, leaving too few cases for subtype analysis here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22.494 kadın bireyin yer aldığı VİTAL çalışmasında (VITamins and Lifestyle) balık tü-ketimi veya besin desteği ile alınan EPA ve DHA'nın hafif şişman ve obez kadınlarda endometriyal (rahim kanseri) kanser riskini artırdığı, normal vücut ağırlığına sahip kadınlarda ise riski azalttığı sonucuna varılmıştır (Brasky, Neuhouser, Cohn, & White, 2014). Deniz ürünleri tüketimi ve prostat kanser gelişimi arasındaki ilişkinin incelendiği bir meta-analizde 31 çalışmanın 17'sinde herhangi bir ilişki bulunmazken, 6'sında riskin azaldığı, 2'sinde ise riskin arttığı gösteril-miş, geriye kalanlarda ise net bir sonuç elde edilmemiştir (Lovegrove et al, 2015).…”
Section: Kanserunclassified